Miglitol attenuates non‐alcoholic steatohepatitis in diabetic patients. Issue 13 (27th July 2018) - Komatsu, Michiharu; Tanaka, Naoki; Kimura, Takefumi; Fujimori, Naoyuki; Sano, Kenji; Horiuchi, Akira; Sugiura, Ayumi; Yamazaki, Tomoo; Shibata, Soichiro; Joshita, Satoru; Umemura, Takeji; Matsumoto, Akihiro; et al.
Abstract : Aim: Postprandial hyperglycemia is frequently accompanied by non‐alcoholic fatty liver disease (NAFLD) and steatohepatitis (NASH). Although α‐glucosidase inhibitors (αGIs) can slow glucose absorption from the intestine and suppress the surge of circulating glucose concentration after meals, it remains unclear whether αGIs are also beneficial for NASH. The aim of this prospective study was to examine the efficacy and safety of miglitol, a typical αGI, for NASH. Methods: Seventeen patients with histologically confirmed NASH and hemoglobin A1c (HbA1c) >6.5% were treated with miglitol (150 mg/day) for 12 months. The changes in clinical parameters and liver histology were analyzed. Results: All patients completed the 12‐month miglitol treatment course with no severe adverse events. The treatment significantly decreased body mass index, serum alanine aminotransferase levels, and HbA1c (all P  < 0.001). Post‐treatment liver biopsy of 11 patients revealed significant improvements in steatosis (from 2.2 ± 0.6 to 1.5 ± 0.7, P  = 0.001), lobular inflammation (from 1.8 ± 0.8 to 1.3 ± 0.5, P  = 0.014), portal inflammation scores (from 0.6 ± 0.5 to 0.1 ± 0.3, P  = 0.025), and NAFLD activity score (from 5.5 ± 1.5 to 3.9 ± 1.4, P  = 0.012). Fibrosis and hepatocyte ballooning scores were unchanged. Conclusions: Miglitol appears to safely ameliorate NASH activity by attenuation of steatosis and lobular/portal inflammation. Appropriately powered controlled trials are warranted to validate our results.